Effects of different proteases on commercial laying hens at peak production - Barbosa,Silvana Alves Pedrozo Vitalino (2020)
ABSTRACT We evaluated the effect of adding proteases in diets of laying hens at peak production on the performance, egg quality, relative weight of digestive organs, and intestinal morphometry. Hy-Line W36 layer hens (390; 28-39 weeks old) were distributed in five treatments, with 13 animals each, with six replicates. The treatments were: control (standard formulation without nutritional reduction or protease inclusion), negative control A - NCA (nutritional reduction according to protease A matrix, without protease), negative control B - NCB (nutritional reduction according to protease B matrix, without protease), NCA + protease A, and NCB + protease B. The experimental period lasted 12 weeks, divided into three cycles of 28 days. Hens subjected to treatments (NCA and NCB) showed a decrease in feed intake. However, the addition of proteases A and B promoted improvement in this trait. The diets NCA and NCB had a negative influence on the production rate of the hens, but the diet supplementation with protease B resulted in significant improvement on egg laying rate. Hens subjected to nutritional reduction presented the worst results regarding mass and conversion by egg mass. However, the addition of enzymes reversed these results. Although the diets did not affect the relative weights of yolk, albumen, eggshell, Haugh unit, and specific gravity of the eggs, a higher eggshell thickness was observed in hens that received NCA, NCB, and NCB + protease B diets. The diets did not influence the relative weights of digestive organs and the small intestine morphometry. Hens fed diets supplemented with A and B have performance recovered in relation to those that received diets with reduced levels of nutrients.